2-D Qsar Analysis of Benzofuran Biphenyl/ Naphthalenes as Potent PTPase-1B Inhibitors - Kaushik, Darpan; Khan, Suroor A (Dhaka University Journal of Pharmaceutical Sciences, 2011)
DOI: 10.3329/dujps.v9i1.7435 Dhaka Univ. J. Pharm. Sci. 9(1): 61-64 2010 (June)